To the question of modern society informatization ant the need of ensuring national information security of Russian Federation at the present stage - A A Galushkin (RUDN Journal of Law, 2014)
In the present article author discuыs questions of informatization and computerization of modern society, as well as problems connected with it. Special attention is given to problem of ensuring information security at the state level (national information security) on the example of Russian Federation. Author considers a number of organizational and legal questions and makes own recommendations on the improvement of work in the field of national information security of Russian Federation.